Gas Chromatography-Mass Spectrometry Fingerprint and in vitro Cytotoxic Studies of Rubus steudneri Leaf Fractions against Michigan Cancer Foundation-7 Breast Cancer Cell Line - Shetty Hallur, Raghavendra Lakshmana [UNESP]; Motamarri, Chaitanya V. N. L.; Ramamoorthy, Prashith Kekuda T.; Murthy, Chetan D.; Siddappa, Ravikumar Patil H.; Bramhanakonda, Vijayananda N. (Wolters Kluwer Medknow Publications, 2021)
Aim: Rubus steudneri Schweinf. (Rosaceae) is one of three Rubus species that grow in Ethiopia. Studies of this species have been restricted to in vitro antioxidant, antidiabetic, and nutritional evaluation. Until today, no identification has been made of its phytochemical fingerprints, resulting in an unclear picture of its phytochemical constituents. This study investigated the phytochemical composition of R. steudneri and its in vitro cytotoxicity against Michigan Cancer Foundation-7 (MCF-7) breast cancer cell lines and Vero cell lines. Materials and Methods: The leaf powder was subjected to liquid-liquid fractionation using n-hexane, chloroform, ethyl acetate, methanol, and water as solvents and the obtained fractions were subjected to flash chromatography and in vitro cytotoxicity studies in MCF-7 cell lines at concentrations from 1 to 1000 mu g/mL, using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Results: The chloroform fraction proved to be the most promising of the bioactive fractions, with 50% of cytotoxicity inhibition for concentrations of 10 mu g/mL on MCF-7 cell lines and 125 mu g/mL on Vero cell lines. Two important drug leads, namely butyl isobutyl phthalate and 2-pyrrolidinone 5-(cyclohexylmethyl), were identified in chloroform fraction using gas chromatography-mass spectrometry (GC-MS) and may be responsible for the in vitro cytotoxicity. Flow cytometer results indicated that the chloroform fraction arrests cell cycle in the sub-G1 phase at a concentration of 100 mu g/mL on MCF-7 cell lines, which proves that metabolites in this fraction may belong to the apoptotic population. Conclusion: In this study, butyl isobutyl phthalate and pyrrolidinone 5-(cyclohexylmethyl), which have significant cytotoxic effects and cell cycle arrest, are extracted. Further in-depth research is in progress to prove the anticancer activity of R. steudneri in search of new leads for anticancer drugs.
Keywords: 2-Pyrrolidinone 5-(cyclohexylmethyl); apoptosis; butyl isobutyl phthalate; cell cycle; flash chromatography